Russia’s economic security in the context of migration processes - O. A. Ageeva; A. B. Yaroshchuk; I. D. Matskulyak (Вестник университета)
The specifics of the migration processes in Russia in the context of ensuring national and economic security of the state has been studied. The purpose of the study is to classify and describe the rapidly increasing threats to the indigenous population associated with the migration processes. The methods of meaningful analysis of online publications and the results of sociological surveys among the population were chosen as the methodology. The migration issue has been revealed, and the available statistical data have been presented and analyzed. The subjects involved in the migration processes are identified both from the side that generates threats to the economic security of Russia and from the side of the government agencies designed to counter these threats. More than 20 specific threats to the economic security of the state have been identified and disclosed. The authors’ definition of the illegal migrant concept has been given, since a significant percentage of migrants who pose threats to the economic security of Russia belong specifically to illegal immigrants who work for shadow businesses and do not pay taxes to the host country’s budget. Illegal migrants do not form the revenue side of the budget, but they claim expenses from it (at least in terms of the maintenance of their large and poor families, medical treatment, and education of their children). The study results indicate that the issue under consideration requires an integrated approach, including an anti-corruption policy against unscrupulous officials, police officers, teachers, and others who want to enrich themselves illegally. The negative consequences of migration issues related to the growing threats to economic security in the state, the low tax culture of entrepreneurs involved in shadow migration schemes, and other persons who commit illegal privileges to migrants for illegal actions have been scaled.